Impact of Antimicrobial Strategies on the Success of Vital Pulp Therapy: A Systematic Review - Setu Katyal; Nitika Gupta; Radhika Sharma; Pooja Bala; Navdeep Kaur; Himani Arora (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Vital pulp therapy (VPT) is a conservative treatment for deep carious lesions in young permanent teeth. Antimicrobial agents are commonly used to reduce bacterial load and prevent secondary infections. Objective: This systematic review aimed to assess the efficacy of various antimicrobial strategies on the success of VPT. Methods: A comprehensive literature search was conducted in electronic databases to identify relevant studies. The quality of included studies was assessed using appropriate tools. Data were extracted and analyzed to evaluate the impact of different antimicrobial agents and techniques on VPT outcomes. Results: The results of the review indicate that antimicrobial agents can significantly contribute to the success of VPT. Conclusion: This systematic review provides a comprehensive overview of the current evidence regarding the efficacy of antimicrobial strategies in VPT.